Formulating Knowledge Management Strategy to Provide Flawless Services (Case Study at PT Flawless’ A&T Department) - Dwi Maryanto; Achmad Ghazali; Rudy Bekti (Jurnal Ilmu Manajemen Advantage, 2023)
PT Flawless Indonesia (PT Flawless) is a leading provider of critical administrative services of Accounting and Tax (A&T), Human Resource and Payroll (HRP), and Global Entity Management (GEM). As aligned with the improved Indonesia’s economic growth after Covid-19 pandemic that attract foreign investors, and the complexity of Indonesia’s regulatory, PT Flawless is benefited from the increasing demand of local assistances to keep the foreign investors in compliant with the local regulations. During 2020 until 2022, PT Flawless recorded satisfactory financial performances as reflected by the increase of Gross Revenue, Gross Profit, and Net Income after Tax. However, A&T Department experiences anomaly since it achieves the highest year-on-year revenue growth but, suffers from the decrease of client satisfaction. This research aims to develop Knowledge Management (KM) strategy to make PT Flawless “famous for flawless services” by increasing client satisfaction and work productivity. This research uses APO KM Assessment Tool to assess KM maturity level of PT Flawless and interview with the Management and staffs to understand the Management’s commitment on KM practice as well as the current states of KM implementation. As the result, currently PT Flawless is at “Refinement” level that it continually assesses and evaluates the KM implementation and seek for improvements. This research proposes PT Flawless to establish a resolute team to manage the KM practice, formalize company policy regarding KM practice, create staffs’ competences map and database, set up regular knowledge sharing, and develop company’s technology to support the KM practice. All of them are aimed to improve PT Flawless’ service excellence and work productivity and at the end, make PT Flawless “famous for flawless services”.